PENINGKATAN PRESTASI BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL PEMBELAJARAN STAD TERINTEGRASI SAINTIFIK MATERI PERUBAHAN WUJUD BENDA PADA PESERTA DIDIK KELAS IV DI SD NEGERI 3 BANCARKEMBAR - Amandariella Samahita Prasetyo; Andri Sulastriningsih; Subuh Anggoro (Journal of Professional Elementary Education, 2023)
The presence of the Science subject has the potential to develop students' capabilities and foster critical thinking skills through both conceptual knowledge and experiments. However, not all knowledge about the universe can be easily comprehended, as many Science learning materials are abstract, requiring students to invest time in absorbing such information. The aim of this research is to improve the learning outcomes of fourth-grade students in the topic of changes in the state of matter at SDN 3 Bancarkembar. This study falls under the category of Classroom Action Research (CAR) conducted in two cycles. The research subjects consist of 17 fourth-grade students. Learning outcome data were collected through tests and subsequently analyzed using descriptive statistics. The results of the research indicate an improvement in learning outcomes related to the topic of unit length in each cycle. The average score in Cycle I was 60.57 and increased to 82.35 in Cycle II. These findings demonstrate that the use of the STAD model integrated with a scientific approach can enhance learning achievement in the topic of unit length in fourth-grade students at SDN 3 Bancarkembar